Post a New Question


posted by .

Make k the subject of the following two equations.

1) 8k+2=3(4k+t)


  • maths -

    8k+2 = 3(4k+t)
    Expand expressions on each side
    8k+2 = 12k + 3t
    Group terms involving k on the left hand side
    8k - 12k = 3t - 2
    -4k = 3t - 2
    Divide both sides by the coefficient of k, do not forget to insert parentheses on the right-hand side:
    k = (3t-2)/-4
    Simply and beautify
    k = -(3t-2)/4
    = (2-3t)/4

    I leave #2 for your exercise, and post your answer for a check if you wish.

Answer This Question

First Name:
School Subject:

Related Questions

More Related Questions

Post a New Question